Use of Paclitaxel to Successfully Treat Children, Adolescents, and Young Adults with Kaposi Sarcoma in Southwestern Tanzania - Hamidu Adinani; Liane Campbell; Nader Kim El-Mallawany; Jeremy Slone; Parth Mehta; Jason Bacha (MDPI AG, 2021)
Treating Kaposi sarcoma (KS) in children, adolescents, and young adults (AYA) remains a challenge in low- and middle-income countries (LMIC) where chemotherapy options and availability are limited. We describe a retrospective cohort review of pediatric patients with KS treated with paclitaxel in Mbeya, Tanzania, between 1 March 2011 and 31 December 2019. Paclitaxel was given to patients who had KS relapse, a contraindication to bleomycin, vincristine, and doxorubicin (ABV), special circumstances in which a clinician determined that paclitaxel was preferable to ABV, or experienced treatment failure, defined as persistent KS symptoms at the completion of treatment. All patients also received multidisciplinary palliative care. Seventeen patients aged 5.1-21.3 years received paclitaxel, of whom 47.1% (8/17) had treatment failure, 29.4% (5/17) received paclitaxel as initial treatment, and 23.5% (4/17) had relapsed. All HIV positive patients (16/17) were given anti-retroviral therapy (ART) and 87.5% (14/16) achieved viral load <1000 cp/mL. At censure, 82.3% (14/17) of patients were alive-71.4% (10/14) achieved complete clinical remission and 28.6% (4/14) achieved a partial response. The median follow up was 37.3 months (range 8.0-83.5, IQR 19.7-41.6), and no patients were lost to follow up. In this cohort, high rates of long-term survival and favorable outcomes were possible with paclitaxel treatment.